Rubber material for supporting transmission shaft and preparation method thereof
By adding components such as lipoic acid @ zinc oxide to the rubber material for transmission shaft support and using vulcanization and pore-generating processes, the problems of existing rubber materials prone to cracking and fatigue damage during high-frequency vibration and thermal oxygen aging are solved. , achieves the improvement of fatigue and aging resistance of the material, extends the service life and improves the NVH performance of the car.
Patent Information
- Application Number
- CN202411414433.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-18
AI Technical Summary
The existing rubber material for transmission shaft support is prone to cracking and fatigue damage during high-frequency vibration and thermal oxygen aging, resulting in a shortened service life and affecting the NVH performance of the car.
Using natural rubber, neoprene, zinc lipoic acid, white carbon black, plasticizer, accelerator DM, sulfur, pore-generating agent and softener, the combination of vulcanization and pore-generating processes is formed to improve fatigue resistance. and rubber materials with aging resistance.
It significantly improves the fatigue and aging resistance of rubber materials, extends service life, reduces transmission shaft vibration and noise, and improves the NVH performance of the car.
Smart Images

Figure BDA0005078973070000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber production, and in particular relates to a rubber material for supporting a transmission shaft and a preparation method thereof. Background Art
[0002] With the rapid development of automobile manufacturing technology, people pay more and more attention to the ride comfort of automobiles. The important content of improving the ride comfort of automobiles is to solve the problems of automobile N (noise), V (vibration), and H (abnormal sound). Due to the characteristics of structure, kinematics and dynamics, the drive shaft inevitably has vibration, which affects the ride comfort of the car. Compared with the vibration caused by other vibration sources, the impact of drive shaft vibration is not significant and did not attract the attention of researchers at first. However, with the continuous increase in vehicle speed and the gradual reduction in the total mass of cars, the problem of drive shaft vibration has become increasingly prominent. Therefore, reducing the vibration of the drive shaft is one of the key links in solving the NVH problem of automobiles.
[0003] Installing a rubber support ring can significantly improve the NVH performance of the drive shaft and improve the ride comfort of the car. It is an effective means to solve the NVH problem of the car. The rubber support ring generally has three functions: supporting, damping and limiting. During long-term use, the rubber support ring will crack and fall off. The main reasons are aging and fatigue. Frictional heat generated during high-frequency vibration accelerates the oxidation of rubber materials, causing aging and cracking of the rubber. In addition, the rubber will undergo structural or performance changes and fatigue damage when subjected to long-term mechanical vibration of the drive shaft, and the cracks will gradually expand. If the rubber support ring is not replaced immediately, the drive shaft will be deformed and damaged, resulting in large vibrations and noise.
[0004] The rubber compound formula is the key factor that determines the fatigue and aging resistance of rubber materials. Natural rubber is widely used as a transmission shaft support and vibration reduction due to its small loss factor, excellent elasticity, fatigue resistance, cold resistance and electrical insulation, and good processing performance. However, natural rubber has the defect of poor heat and oxidation resistance and is prone to aging and deterioration, which greatly shortens its service life. Summary of the invention
[0005] The object of the present invention is to provide a rubber material for supporting a transmission shaft and a preparation method thereof, so as to improve the aging resistance of the rubber material and prolong its service life.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] The present invention provides a rubber material for supporting a transmission shaft, which comprises the following components by weight:
[0008] 70-80 parts of natural rubber, 20-30 parts of chloroprene rubber, 10-20 parts of lipoic acid@zinc oxide, 15-25 parts of white carbon black, 1-3 parts of plasticizer, 2-4 parts of accelerator DM, 1.5-3.5 parts of sulfur, 0.1-0.3 parts of porogen, and 4-6 parts of softener.
[0009] Furthermore, the rubber material comprises the following components by weight: 75 parts of natural rubber, 25 parts of chloroprene rubber, 10-20 parts of lipoic acid@zinc oxide, 15 parts of white carbon black, 1 part of plasticizer, 4 parts of accelerator DM, 3 parts of sulfur, 0.1-0.3 parts of porogen, and 4 parts of softener.
[0010] The porogen can form micropores inside the rubber material through endothermic decomposition. The microporous structure can effectively avoid cracking caused by stress concentration during the vibration of the rubber material. A small amount of porogen can prevent the formation of too many holes in the rubber material that makes it difficult to support the drive shaft, ensuring that the rubber material does not deform during the vibration process and has a limiting effect.
[0011] Furthermore, the lipoic acid@zinc oxide is zinc oxide modified with lipoic acid, wherein the loading amount of lipoic acid is 6-18wt%;
[0012] Furthermore, the preparation method of the lipoic acid@zinc oxide is as follows:
[0013] The lipoic acid was dissolved in an ethanol solution with a mass concentration of 40%, and then mesoporous zinc oxide was added into the solution and stirred to obtain a reaction solution. The solution was reacted at a constant temperature of 60° C. for 1 hour. After the reaction was completed, the solution was centrifuged to obtain a precipitate. The precipitate was dried to obtain lipoic acid-modified zinc oxide.
[0014] There is a carboxyl group on the side chain of lipoic acid. Through the reaction between the carboxyl group and zinc oxide, lipoic acid is anchored in the microporous structure of mesoporous zinc oxide, and zinc oxide can protect lipoic acid.
[0015] Furthermore, the porogen is a bicarbonate foaming agent.
[0016] Furthermore, the softener is coumarone resin.
[0017] The present invention also provides a method for preparing a rubber material for supporting a transmission shaft, comprising the following steps:
[0018] (1) weighing natural rubber and putting it into an open mill for mastication, and weighing chloroprene rubber and putting it into another open mill for mastication, respectively forming a natural rubber masterbatch and a chloroprene rubber masterbatch;
[0019] (2) The natural rubber masterbatch and the chloroprene rubber masterbatch were left standing for 8 hours, put into a mixer, white carbon black, plasticizer and softener were added, lipoic acid and zinc oxide were added after mixing for 15 minutes, and the mixing was continued for 10 minutes, thinned 5 times, and left standing for 10 hours;
[0020] The lipoic acid in lipoic acid@zinc oxide has a disulfide five-ring structure, which can react with some double bonds in rubber to connect the rubber molecular chains and promote the vulcanization process. The more sulfur atoms there are, the more polysulfide cross-linking bonds are formed, and the cross-linking density increases, which can improve the fatigue resistance of rubber materials. The disulfide five-ring structure has significant electrophilicity and the ability to react with free radicals, which can scavenge free radicals. During the thermal oxidative aging process of rubber, it can destroy the oxidation chain reaction and inhibit thermal oxidative aging.
[0021] (3) After parking, the rubber is put into a vulcanizer, sulfur, accelerator DM, softener and pore-forming agent are added, and the rubber material is obtained after vulcanization.
[0022] When two rubbers are blended, when the cohesive energy difference between the two is large, the island phase molecules tend to shrink and clump together, and there is an obvious interface with the sea phase molecules. Natural rubber and chloroprene rubber have poor compatibility. Separating the two into masterbatches and then mixing them can effectively improve the mixing processing performance.
[0023] Furthermore, the natural rubber has a plasticizing temperature of 50° C. and a plasticizing time of 3 minutes, and the chloroprene rubber has a plasticizing temperature of 40° C. and a plasticizing time of 2 minutes.
[0024] Furthermore, the mixing temperature of the mixer is 80°C.
[0025] Furthermore, the vulcanization in the vulcanizer is divided into two stages, the first stage vulcanization temperature is 120° C., the vulcanization time is 5 min, the second stage vulcanization temperature is 150° C., the vulcanization time is 10 min, and the clamping pressure is 10 MPa.
[0026] Beneficial effects of the present invention:
[0027] (1) By adding thioctic acid@zinc oxide material to the rubber material, the thioctic acid molecules are anchored in the micropores of mesoporous zinc oxide through chemical action. While zinc oxide protects the thioctic acid molecules, the disulfide pentacyclic structure based on thioctic acid participates in the cross-linking of the rubber, so that the zinc oxide can be fully dispersed. Zinc oxide can further promote vulcanization. The two synergistically improve the fatigue resistance of the rubber material; the disulfide pentacyclic structure of thioctic acid has the function of removing free radicals, which can inhibit the thermal oxidation reaction of rubber, and zinc oxide can improve the thermal conductivity of rubber, help dissipate heat, reduce the rate of thermal oxidation reaction, and extend the service life of the rubber material.
[0028] (2) A small amount of porogen is added to the rubber material to form some micropores inside the rubber material. The small cavity structure is conducive to dispersing external forces, alleviating the transmission of vibration, and avoiding cracking caused by severe vibration during the process of supporting the transmission shaft. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] This embodiment provides a rubber material for supporting a transmission shaft, which includes the following components by weight:
[0032] 75 parts of natural rubber, 25 parts of chloroprene rubber, 10 parts of lipoic acid@zinc oxide, 15 parts of white carbon black, 1 part of aromatic oil, 4 parts of accelerator DM, 3 parts of sulfur, 0.1 parts of sodium bicarbonate, and 4 parts of coumarone resin.
[0033] Preparation of lipoic acid@zinc oxide:
[0034] Thioctic acid was dissolved in an ethanol solution with a mass concentration of 40% at a concentration of 0.5 g / L, and mesoporous zinc oxide was added to the solution and stirred to obtain a reaction solution. The concentration of mesoporous zinc oxide in the reaction solution was 7.5 g / L and the reaction was carried out at a constant temperature of 60°C for 1 hour. After the reaction was completed, the precipitate was obtained by centrifugation. The precipitate was dried to obtain thioctic acid@zinc oxide, wherein the loading amount of thioctic acid was 6 wt%.
[0035] Preparation of rubber material:
[0036] (1) weighing natural rubber and putting it into an open mill for mastication at 50° C. for 3 min, and weighing chloroprene rubber and putting it into another open mill for mastication at 40° C. for 2 min, respectively forming a natural rubber masterbatch and a chloroprene rubber masterbatch;
[0037] (2) The natural rubber masterbatch and the chloroprene rubber masterbatch were left standing for 8 hours, put into a mixer, set the mixer temperature to 80°C, added with white carbon black, aromatic oil and coumarone resin, mixed for 15 minutes, then added with lipoic acid@zinc oxide, continued to mix for 10 minutes, thinned 5 times, and left standing for 10 hours;
[0038] (3) After parking, put it into the vulcanizer, add sulfur, accelerator DM, softener and pore-forming agent, set the clamping pressure to 10 MPa, the vulcanization temperature to 120°C, adjust the vulcanization temperature to 150°C after vulcanization for 5 minutes, continue vulcanization for 10 minutes, and obtain the rubber material after vulcanization.
[0039] Example 2
[0040] The difference from Example 1 is that the loading amount of lipoic acid in the prepared lipoic acid@zinc oxide is 15wt%, and the other steps are the same as Example 1. The specific steps for preparing lipoic acid@zinc oxide are as follows:
[0041] Thioctic acid was dissolved in an ethanol solution with a mass concentration of 40% at a concentration of 1.5 g / L, and mesoporous zinc oxide was added to the solution and stirred to obtain a reaction solution. The concentration of mesoporous zinc oxide in the reaction solution was 10.5 g / L, and the reaction was carried out at a constant temperature of 60°C for 1 hour. After the reaction was completed, the precipitate was obtained by centrifugation. The precipitate was dried to obtain thioctic acid@zinc oxide, wherein the loading amount of thioctic acid was 15 wt%.
[0042] Example 3
[0043] The difference from Example 1 is that the loading amount of lipoic acid in the prepared lipoic acid@zinc oxide is 18wt%, and the other steps are the same as Example 1. The specific steps for preparing lipoic acid@zinc oxide are as follows:
[0044] Thioctic acid was dissolved in an ethanol solution with a mass concentration of 40% at a concentration of 2.0 g / L, and mesoporous zinc oxide was added to the solution and stirred to obtain a reaction solution. The concentration of mesoporous zinc oxide in the reaction solution was 11 g / L and the reaction was carried out at a constant temperature of 60°C for 1 hour. After the reaction was completed, the solution was centrifuged to obtain a precipitate. The precipitate was dried to obtain thioctic acid@zinc oxide, wherein the loading amount of thioctic acid was 18 wt%.
[0045] Example 4
[0046] The difference from Example 1 is that the amount of lipoic acid@zinc oxide added to the rubber material is 15 parts, and the other steps are the same as Example 1.
[0047] Example 5
[0048] The difference from Example 1 is that the amount of lipoic acid@zinc oxide added to the rubber material is 20 parts, and the other steps are the same as Example 1.
[0049] Example 6
[0050] The difference from Example 1 is that the amount of sodium bicarbonate added to the rubber material is 0.2 parts, and the other steps are the same as Example 1.
[0051] Example 7
[0052] The difference from Example 1 is that the amount of sodium bicarbonate added to the rubber material is 0.3 parts, and the other steps are the same as Example 1.
[0053] Comparative Example 1
[0054] Compared with Example 1, zinc oxide is used to replace lipoic acid@zinc oxide in the rubber material component provided in this comparative example, and other steps are the same as those in Example 1.
[0055] Comparative Example 2
[0056] Compared with Example 1, the rubber material component provided in this comparative example is replaced with lipoic acid@zinc oxide by lipoic acid, and the other steps are the same as Example 1.
[0057] Comparative Example 3
[0058] Compared with Example 1, the rubber material component provided in this comparative example does not include lipoic acid@zinc oxide, and the other steps are the same as Example 1.
[0059] Comparative Example 4
[0060] Compared with Example 1, the rubber material component provided in this comparative example does not include sodium bicarbonate, and the other steps are the same as Example 1.
[0061] Comparative Example 5
[0062] Compared with Example 1, the rubber material components provided in this comparative example do not include lipoic acid@zinc oxide and sodium bicarbonate, and the other steps are the same as those in Example 1.
[0063] Performance tests were performed on Examples 1 to 7 and Comparative Examples 1 to 5, and the results are shown in Table 1:
[0064] The dynamic fatigue resistance test is tested with reference to "GB / T 1687.4-2021 Determination of temperature rise and fatigue resistance of vulcanized rubber in flexure test Part 4: Constant stress flexure test".
[0065] The aging resistance test is carried out with reference to GB / T 3512-2014 Hot air accelerated aging and heat resistance test for vulcanized rubber or thermoplastic rubber.
[0066] The compression set rate test is carried out in accordance with GB / T 7759.1-2015 Determination of compression set of vulcanized rubber or thermoplastic rubber Part 1: At room temperature and high temperature conditions.
[0067] The ozone resistance test is tested with reference to "GB / T 13642-2015 Dynamic tensile test for ozone crack resistance of vulcanized rubber or thermoplastic rubber".
[0068] Table 1
[0069]
[0070] As can be seen from Table 1, compared with Example 1, the amount of lipoic acid in lipoic acid @ zinc oxide is increased in Example 2 and Example 3, and the fatigue resistance and heat-oxidative aging resistance of the rubber material are improved. In Example 3, due to excessive lipoic acid loading, the contact surface between zinc oxide and the rubber material is reduced, and the rubber vulcanization cannot be better promoted. On the basis of Example 1, Example 4 and Example 5 increase the amount of lipoic acid @ zinc oxide added in the rubber material, and its overall performance is greatly improved; in Example 6 and Example 7, the amount of porogen added is increased. When 0.2 parts of sodium bicarbonate are added in Example 6, the comprehensive performance of the rubber material is better than that of Example 7. In Example 7, the deformation rate of the rubber material will increase when too much porogen is added, which is not conducive to supporting the transmission shaft. The performance of the rubber material of Comparative Examples 1-Comparative Examples 5 is greatly reduced compared with that of Example 1, especially after lipoic acid @ zinc oxide and sodium bicarbonate are not added in Comparative Example 5, the fatigue resistance, aging resistance and ozone oxidation resistance of the rubber material are all poor, which is not conducive to the vibration reduction and protection of the transmission shaft support material, and is prone to aging and cracking, and has a short service life.
[0071] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A rubber material for supporting a transmission shaft, characterized in that: By weight, it includes the following components: 70-80 parts of natural rubber, 20-30 parts of chloroprene rubber, 10-20 parts of lipoic acid@zinc oxide, 15-25 parts of white carbon black, 1-3 parts of plasticizer, 2-4 parts of accelerator DM, 1.5-3.5 parts of sulfur, 0.1-0.3 parts of porogen, and 4-6 parts of softener.
2. The rubber material for supporting a transmission shaft according to claim 1, characterized in that: The rubber material comprises the following components by weight: 75 parts of natural rubber, 25 parts of chloroprene rubber, 10-20 parts of lipoic acid@zinc oxide, 15 parts of white carbon black, 1 part of plasticizer, 4 parts of accelerator DM, 3 parts of sulfur, 0.1-0.3 parts of porogen, and 4 parts of softener.
3. The rubber material for supporting a transmission shaft according to claim 1, characterized in that: The lipoic acid@zinc oxide is zinc oxide loaded with lipoic acid, wherein the loading amount of lipoic acid is 6-18 wt %.
4. The rubber material for supporting a transmission shaft according to claim 1, characterized in that: The preparation method of the lipoic acid@zinc oxide is as follows: Dissolve lipoic acid in 40% ethanol solution, add mesoporous zinc oxide into the solution and stir to mix evenly to obtain a reaction solution, keep the temperature at 60°C for 1 hour, centrifuge to obtain a precipitate after the reaction is completed, and dry the precipitate to obtain lipoic acid@zinc oxide.
5. The rubber material for supporting a transmission shaft according to claim 1, characterized in that: The pore-forming agent is a bicarbonate foaming agent.
6. The rubber material for supporting a transmission shaft according to claim 1, characterized in that: The softener is coumarone resin.
7. A method for preparing the rubber material for supporting a transmission shaft according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) weighing natural rubber and putting it into an open mill for mastication, and weighing chloroprene rubber and putting it into another open mill for mastication, respectively forming a natural rubber masterbatch and a chloroprene rubber masterbatch; (2) The natural rubber masterbatch and the chloroprene rubber masterbatch were left standing for 8 hours, put into a mixer, white carbon black, plasticizer and softener were added, lipoic acid and zinc oxide were added after mixing for 15 minutes, and the mixing was continued for 10 minutes, thinned 5 times, and left standing for 10 hours; (3) After parking, the rubber is put into a vulcanizer, sulfur, accelerator DM, softener and pore-forming agent are added, and the rubber material is obtained after vulcanization.
8. The method for preparing a rubber material for supporting a transmission shaft according to claim 7, characterized in that: The natural rubber has a plasticizing temperature of 50° C. and a plasticizing time of 3 minutes, while the chloroprene rubber has a plasticizing temperature of 40° C. and a plasticizing time of 2 minutes.
9. The method for preparing a rubber material for supporting a transmission shaft according to claim 7, characterized in that: The mixing temperature of the mixer is 80°C.
10. The method for preparing a rubber material for supporting a transmission shaft according to claim 7, characterized in that: The vulcanization in the vulcanizer is divided into two stages, the first stage vulcanization temperature is 120° C., the vulcanization time is 5 min, the second stage vulcanization temperature is 150° C., the vulcanization time is 10 min, and the clamping pressure is 10 MPa.
Citation Information
Cited By
Environment-friendly high-dispersion combined active agent for rubber and preparation method of environment-friendly high-dispersion combined active agent
CN121045647A